Resilience Development in Qur'an Memorization Students at an Islamic Boarding School - Azmi Luthfia; Fajar Kawuryan (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to understand in depth how resilience is formed and developed through students' experiences memorizing the Qur'an in an Islamic boarding school, and how these experiences affect their psychological well-being and academic success. The study used a qualitative, phenomenological approach, involving three students from the Futuhul Qur'an Islamic Boarding School, selected through purposive sampling. Data were collected through semi-structured interviews and structured observations, then analyzed through data reduction, presentation, and verification. The results of the study show that resilience develops through the interaction of three factors from Grotberg: external support (I Have), personal strength (I Am), and interpersonal skills and problem-solving (I Can), which collaborate to overcome memorization difficulties and achieve psychological well-being. This finding also shows that religiosity influences the formation of resilience. The novelty of this study lies in its phenomenological exploration, using Grotberg's theory, that reveals unique spiritual-emotional mechanisms in the formation of student resilience. These findings reinforce the need to strengthen the training and support system in Islamic boarding schools.